Dietary behaviour of pregnant women with anaemia in Bangladesh - Khatun, Salma; Saha, Ashees Kumar; Park, Seungmi; Siddika, Aysha; Sultana, Papia; Khatun, Fahmida (Asian Journal of Medical and Biological Research, 2021)
In pregnancy a healthy dietary behavior is beneficial for the expecting mother and her fetus. Anemia is one of the most common nutritional deficiency disorders that can be prevented through promoting dietary behavior. The aim of this study is to examine the dietary behavior of pregnant woman with anemia in Bangladesh. A descriptive cross-sectional study design was applied. By using G* Power, 135 pregnant women were purposively recruited from MMCH, Dhaka. Data was analyzed by using descriptive statistics and inferential statistics, independent t-test and one way ANOVA. Findings showed the mean age of the participants was 25 (SD=4.96) years. Multi gravida was 55.6% and 68.1% reported their medium healthy condition. The average dietary behavior reported 56.03 (SD=6.15) and 67.4% participants’ hemoglobin concentration were within 10-10.9 g/dl. In bivariate analysis, finding showed that anemia has significantly related with age (F = 12.88, p < 001), level of education (F = 2.92, p = .036), income (r = 0.19, p = .027), gravida (F = 5.63, p = .004) health condition (F = 10.89, p < 001). The result of dietary behaviors showed that anemia has positively correlated (r = 0.21, p = .017) with dietary behavior. Dietary behavior is related with some factors, age, low level education, grand multi and primiparous, poor health condition found less hemoglobin concentration indicate as less dietary intake. Monthly income and dietary behavior impact in increasing Hemoglobin concentration. In this regards, maternal nurses might play a vital role for providing nursing intervention to improve pregnant women’s dietary behavior. Asian J. Med. Biol. Res. December 2020, 6(4): 674-682